Can the combination of deep tissue massage and stretching influence the recovery process of lower back pain injuries? - Liza; Bafirman; Masrun; Y Touvan Juni Samodra; Mikkey Anggara Suganda; Muhamad Sazeli Rifki; Didi Suryadi; Ardo Okilanda; Danang Dwi Purwanto; Youssouf Haïdara (Universidad de Murcia, 2024)
Lower Back Pain (LBP) presents as discomfort in the lumbar region, leading to movement limitations. Addressing LBP requires specialized treatment to alleviate pain. The aim of this study was to demonstrate the effectiveness of combining deep tissue massage and stretching in healing low back pain injuries. This study adopted a pre-experimental design, employing a one-group pretest and posttest approach. The initial assessments (pretests) gauged LBP severity using VAS, Modified Schober Test, Fingertip to Floor, and ODI. Subsequently, a combination therapy of deep tissue massage and stretching is administered three times weekly over three weeks. Final assessments (posttest) are conducted. Participants, recruited from the LKP Rumah Sehat Mandiri clinic over the past five months, consisted of 20 individuals aged 20-60 years, sampled purposively. The study revealed significant improvements in pain, flexion, extension, right flexion, left flexion, and functional indicators following the combination therapy, with a significance value of 0.000, indicating a profound effect (p < 0.05). Notably, left flexion demonstrated a significance value of 0.001, further affirming the treatment's efficacy. The findings support the effectiveness of combining deep tissue massage and stretching in reducing LBP severity and promoting healing. Thus, this combined approach holds promise for managing LBP injuries effectively.